Dynamical downscaling of prevailing synoptic-scale winds over the complex terrain of Mariepskop, South Africa - Pretorius, I.I; Rautenbach, H (Clean Air Journal, 2013)
Locations where large altitudinal gradients exist have been shown to be a good early indicator of climate change. Mariepskop is a high mountain peak situated in the Mpumalanga province of South Africa. It is partly isolated from the rest of the Drakensberg mountain range, making it ideal to study the effects of flow dynamics and climate over the mountain without interference in the flow from adjacent topography. The flow dynamics of Mariepskop was studied by forcing averaged, long term synoptic observations at Mariepskop across the lateral boundaries of a Computational Fluid Dynamics (CFD) model. Although CFD models have traditionally been used for engineering applications, CFD models have been used more commonly in the meteorological realm over the last few years. Model results were verified by weather station observations and aerial photographs of the mountain. The model was able to simulate wind speed, wind direction and high rainfall areas relatively well.